Improvement in the sensitivity of newborn screening for Fabry disease among females through the use of a high-throughput and cost-effective method, DNA mass spectrometry. Issue 1 (January 2018) - Lu, Yung-Hsiu; Huang, Po-Hsun; Wang, Li-Yun; Hsu, Ting-Rong; Li, Hsing-Yuan; Lee, Pi-Chang; Hsieh, Yu-Ping; Hung, Sheng-Che; Wang, Yu-Chen; Chang, Sheng-Kai; Lee, Ya-Ting; Ho, Ping-Hsun; et al.
Abstract Many female carriers of Fabry disease are likely to develop severe morbidity and mortality. However, by our own estimation, around 80% of female newborns are missed by our current enzyme-based screening approach. Our team's aim was to develop an improved cost-effective screening method that is able to detect Fabry disease among female newborns. In Taiwan, based on a database of 916, 000 newborns, ~98% of Fabry patients carry mutations out of a pool of only 21 pathogenic mutations. An Agena iPLEX platform was designed to detect these 21 pathogenic mutations using only a single-assay panel. A total of 54, 791 female infants were screened and 136 female newborns with the IVS4 + 919G > A mutation and one female newborn with the c.656T > C mutation were identified. Using the current enzyme-based newborn screening approach as baseline, around 83% of female newborns are being missed. Through a family study of the IVS4 female newborns, 30 IVS4 adult family members were found to have left ventricular hypertrophy. Ten patients received endomyocardial biopsy and all were found to have significant globotriaosylceramide (Gb3) accumulation in their cardiomyocytes. All of these individuals now receive enzyme replacement therapy. We have demonstrated that the Agena iPLEX assay is a powerful tool for detecting females with Fabry disease. Furthermore, through this screening, we also have been able to identify many disease-onset adult family members who were originally undiagnosed for Fabry disease. This screening helps them to receive treatment in time before severe and irreversible cardiac damage has occurred.